THE EFFECT OF SULFUR – CONTAINING COMPOUNDS ON THE STABILITY OF DIESEL FUELS - Zuhdan Fathoni. A; Batts. B. D; Sprecher. R. F; Veloski. G (Scientific Contributions Oil and Gas, 1991)
A high-resolution low-voltage mass spectrometric study has been carried out on the sulfur-containing fractions of fresh diesel fuel and on samples aged at 43°C in borosilicate bootles (ASTM D 4625 test) for periods of 6.5, 13, 19,5 and 26 weeks, and at 80°C for periods of 0.5, 1, 1.5,  2, 3, and 4 weeks. Homologous series of benze-and di benzothiophenes are the principal sulphur-containing compounds were detected. The concentrations of all species present with aging were monitored and the role of each compound in the gum-forming process assessed.